Proteases and their inhibitors in cancer metastasis;vol-4 - Foidart, Jean Michel;Ed. Muschel, Ruth J;Ed (Kluwer Academic Publishers, 2002)
This volume offers an update on this aspect of cancer treatment, its interest bias and possible clinical implications, providing an evaluation of the mechanisms of action of proteases and their inhibitors in tumour biology.